2016
DOI: 10.1186/s13568-016-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two new keratinolytic proteases from a Bacillus pumilus strain using protein analysis and gene sequencing

Abstract: The Bacillus strain (CCUG 66887) has a high capacity to excrete keratinase with the ability to degrade both alpha- and beta keratin. In this study we aimed to show the characteristics of the keratinolytic protease and to identify its gene by using liquid chromatography–electrospray ionization tandem mass spectrometry methods (nanoHPLC–ESI–MS/MS) followed by Mascot data base search. The results showed that the enzyme in fact consists of two different keratinases, both with a molecular mass of 38 kDa. Further, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
2
15
0
3
Order By: Relevance
“…To date, by using different assays (see Section 3.2 ), keratinolytic enzymes have been shown to be produced by both bacteria and fungi. Some of the prominent producers are bacterial species, such as B. licheniformis , B. subtilis, and B. pumilus ( Fellahi et al, 2016 ; Gupta and Singh, 2013 ; Ramnani and Gupta, 2004 ), as well as actinobacteria, such as Streptomyces fradiae , Nocardiopsis sp. ( Li et al, 2007 ; Mitsuiki et al, 2004 ).…”
Section: Keratinolytic Enzymes and Keratinase Assaysmentioning
confidence: 99%
“…To date, by using different assays (see Section 3.2 ), keratinolytic enzymes have been shown to be produced by both bacteria and fungi. Some of the prominent producers are bacterial species, such as B. licheniformis , B. subtilis, and B. pumilus ( Fellahi et al, 2016 ; Gupta and Singh, 2013 ; Ramnani and Gupta, 2004 ), as well as actinobacteria, such as Streptomyces fradiae , Nocardiopsis sp. ( Li et al, 2007 ; Mitsuiki et al, 2004 ).…”
Section: Keratinolytic Enzymes and Keratinase Assaysmentioning
confidence: 99%
“…Thus, keratinous materials can remain inert in the environment for a long time, as keratinase producing microorganisms are not widespread (Lange et al 2016). However, despite their rigid structure, keratins are recycled in nature and can be efficiently degraded by a few microorganisms such as bacteria from the genus Bacillus (Fellahi et al 2016), Streptomyces (Ramakrishnan et al 2011) from several species of fungi (El-Gendy 2010; Duarte et al 2011;Bohacz 2017) and from Archaea (Kublanov et al 2009;Brandelli et al 2010) that are capable of producing keratinolytic peptidases known as keratinases.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, keratinases are proteolytic enzymes (peptidases or proteases) that are capable of cleaving peptide bonds Responsible Editor: Inês Conceição Roberto in keratin [8]. Most studies on keratinases have mainly identified and characterized the alkaline monomeric serine peptidases [9][10][11][12][13][14][15][16][17][18] and less frequently, the alkaline monomeric metallopeptidases [19][20][21][22][23]. Some studies have also described aspartic keratinases isolated from yeasts [24,25] and dimeric keratinases [13].…”
Section: Introductionmentioning
confidence: 99%